2015
DOI: 10.1681/asn.2013111185
|View full text |Cite
|
Sign up to set email alerts
|

Paricalcitol for Secondary Hyperparathyroidism in Renal Transplantation

Abstract: Secondary hyperparathyroidism contributes to post-transplant CKD mineral and bone disorder. Paricalcitol, a selective vitamin D receptor activator, decreased serum parathyroid hormone levels and proteinuria in patients with secondary hyperparathyroidism. This single-center, prospective, randomized, crossover, open-label study compared the effect of 6-month treatment with paricalcitol (1 mg/d for 3 months and then uptitrated to 2 mg/d if tolerated) or nonparicalcitol therapy on serum parathyroid hormone levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
2
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 46 publications
2
43
2
3
Order By: Relevance
“…Another randomized controlled trial of paricalcitol vs no treatment for 6 mo in prevalent KT recipients with transplant duration 517 years also revealed the ability of paricalcitol in lowering PTH. In this study, vertebral BMD as well as proteinuria improved after paricalcitol therapy [81] . The above evidence indicate that oral active vitamin D are beneficial in alleviating persistent hyperparathyroidism and improving bone mass.…”
Section: Vitamin Dsupporting
confidence: 53%
“…Another randomized controlled trial of paricalcitol vs no treatment for 6 mo in prevalent KT recipients with transplant duration 517 years also revealed the ability of paricalcitol in lowering PTH. In this study, vertebral BMD as well as proteinuria improved after paricalcitol therapy [81] . The above evidence indicate that oral active vitamin D are beneficial in alleviating persistent hyperparathyroidism and improving bone mass.…”
Section: Vitamin Dsupporting
confidence: 53%
“…In the same study, moderate renal allograft fibrosis was reduced in the paricalcitol group compared with the control group. Another randomized, crossover study has shown that paricalcitol also reduced bone remodeling as reflected by reduction of bALP and osteocalcin together with improvements in lumbar spine BMD (34). Interestingly, there was a reduction in eGFR associated with paricalcitol therapy, but it is not clear whether this reflects changes in creatinine secretion and generation or a direct effect on GFR.…”
Section: Vitamin D and Vitamin D Analogsmentioning
confidence: 99%
“…Согласно при-лагаемой к парикальцитолу инструкции, препарат не рекомендован для коррекции посттрансплан-тационного ГПТ. В последние годы опубликовано всего несколько работ, показавших одинаковые эф-фективность и безопасность парикальцитола в про-филактике и лечении ГПТ у реципиентов почечного трансплантата [32][33][34]. Авторы убедительно проде-монстрировали, что парикальцитол (пероральная форма в дозе 1-2 мкг/сут -3-4 мкг/нед.)…”
Section: лечение посттрансплантационного гптunclassified